BALI CATTLE DEVELOPMENT STRATEGY BASED ON THE RESULTS OF PALM OIL PLANTATION IN KOLAKA DISTRICT - Zulkarnain, Deki; Munadi, La Ode; Pagala, M.Amrullah; Kasmin, Muh. Obi (Pascasarjana Universitas Sulawesi Tenggara, 2020)
The strategy of developing Bali cattle and oil palm plantations is carried out to increase income as well as one of the strategic efforts in overcoming the limitations of animal feed faced by farmers. The strategy of developing Bali cattle farms in oil palm plantations is directed at the development of the cattle breeding industry, fattening industries and by-products of animal feed-based products and by-products of palm oil as a center for cattle development in the context of revitalizing and accelerating sustainable livestock development. The purpose of this study is to analyze the development strategy of Bali cattle based on oil palm plantations. The analysis tools used are L/Q (Location Questions), Carrying Capacity and SWOT analysis (Strength, Weakness, Opportunity, Threat). The results showed that the Kolaka Regency has the potential as a center for the development of Bali cattle based on the results of oil palm plantations.Â